2019
DOI: 10.3390/ijms20092076
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptomic Analysis of Biological Process and Key Pathway in Three Cotton (Gossypium spp.) Species Under Drought Stress

Abstract: Drought is one of the most important abiotic stresses that seriously affects cotton growth, development, and production worldwide. However, the molecular mechanism, key pathway, and responsible genes for drought tolerance incotton have not been stated clearly. In this research, high-throughput next generation sequencing technique was utilized to investigate gene expression profiles of three cotton species (Gossypium hirsutum, Gossypium arboreum, and Gossypium barbadense L.) under drought stress. A total of 696… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 97 publications
(120 reference statements)
0
13
0
Order By: Relevance
“…The overexpression of OsPYL3 and OsPYL9 genes can increase rice tolerance to drought [51], and NtPYLs have been shown to have important functions in the drought tolerance of Nicotiana tabacum [52]. Highthroughput next generation sequencing showed that PYL, PP2C, and SRK2E respond to drought stress in Gossypium spp [53]. In banana, the PYL-PP2C-SnRK2 gene family regulated its tolerance to abiotic stress, such as salt and drought stress conditions [54].…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of OsPYL3 and OsPYL9 genes can increase rice tolerance to drought [51], and NtPYLs have been shown to have important functions in the drought tolerance of Nicotiana tabacum [52]. Highthroughput next generation sequencing showed that PYL, PP2C, and SRK2E respond to drought stress in Gossypium spp [53]. In banana, the PYL-PP2C-SnRK2 gene family regulated its tolerance to abiotic stress, such as salt and drought stress conditions [54].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, other studies also put light on the role of various pathways such as plant hormones signal transduction pathway, proline metabolism pathway, starch and sucrose metabolism pathway etc. in response to drought stress [25][26][27][28]. The complete and comprehensive physiological, anatomical, biochemical and transcriptomic analyses are rare under drought stress in flue-cured tobacco cultivars.…”
Section: Introductionmentioning
confidence: 99%
“…bZIP11, bZIP17, bZIP37, bZIP47, bZIP53, bZIP55 and bZIP60 etc. (Yao et al 2011;Ranjan et al 2012;Zhang et al 2013;Peng et al 2014;Zhang et al 2018;Hasan et al 2019;Wang et al 2020).…”
Section: Brlz Domain Structural Characterization Of G Raimondii Bzip Proteins N-x7-r/k Basic Regionmentioning
confidence: 99%